Genome-wide identification of β-1,3-glucanase genes in Hevea brasiliensis - Xin, Jie Lui; Thottathil, Gincy P.; Kumar Sudesh, (Penerbit Universiti Kebangsaan Malaysia, 2023)
β-1,3-glucanase is one of the pathogenesis-related proteins well-known for their antifungal properties which can be abundantly found in Hevea brasiliensis. Utilization of β-1,3-glucanase in the genetic improvement of H. brasiliensis is very important as the high susceptibility to various fungal infections has challenged the current natural rubber industry. A few nucleotide sequences for β-1,3-glucanase have been reported and their role in biotic stress management has been demonstrated. Being a multigene family, it is necessary to identify and characterize more isoforms of β-1,3-glucanase to select the most suitable isoform to be utilized in genetic improvement. In the current study, we conducted a genome-wide identification of β-1,3-glucanases in H. brasiliensis, their classification based on the functional domains and phylogenetic analysis, using different bioinformatics tools. All publicly available nucleotide sequences were collected and curated by eliminating sequences that lack glycoside hydrolase family 17 (GH 17) domain as well as the partial and closely identical sequences and obtained 14 full-length sequences. The sequences were categorized into 4 distinct classes (I-IV) based on their functional domains and C-terminal extension. Class III and IV which lack the carbohydrate-binding C-terminal X8 domain are the largest classes identified with 5 β-1,3-glucanase each while 4 β-1,3-glucanase contain a variable C-terminal X8 domain. Phylogenetic analysis showed the clustering of β-1,3-glucanases into six major clades (I-VI) based on the domains. Clades I and II were identified as the largest clades with 4 β-1,3-glucanase in each. Several paralogous clusters have been observed for H. brasiliensis indicating the gene family expansion within the species or in the immediate ancestors with possible species-specific function. Further functional characterization is necessary to select the suitable gene to be utilized in genetic improvement and the present study provides a platform for it.